Cytotoxicity and immunostimulation: double attack on cancer cells with polymeric therapeutics - Ríhová, Blanka; Kovár, Lubomír; Kovár, Marek; Hovorka, Ondrej (Trends in biotechnology, 2009)
The successful treatment of cancer with conventional drugs is frequently complicated by the resistance of tumor cells to such a non-specific therapy. Over the last few years, immunotherapy has gained attention as a tumor-specific approach. Recent findings demonstrated that some conventional cytostatics stimulate local anticancer responses. New anticancer drugs, including their polymeric derivatives, are currently being developed with the aim of destroying tumors more effectively and more specifically. Among these, the water-soluble conjugates of doxorubicin with N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer carrier have emerged as efficient therapeutics because they are able to not only directly destroy cancer cells but also elicit systemic tumor-specific anticancer responses. Here, we discuss new insights into their mechanisms of immune surveillance, which could suggest novel approaches to cancer therapy.
Keywords: Polymers; Immunologic Factors; Adjuvants, Immunologic; nádory; Animals; lidé; imunologické faktory; protinádorové látky; biologické modely; polymery; Cytotoxins; Neoplasms; Humans; adjuvancia imunologická; zvířata; Antineoplastic Agents; Models, Biological; cytotoxiny